Combined computational/experimental investigation of new cocrystals of the drug bosentan. Issue 28 (29th June 2022) - Barbas, Rafael; Portell, Anna; Hunter, Christopher A.; Prohens, Rafel; Frontera, Antonio
Abstract : This manuscript reports the discovery of new cocrystals of bosentan, a drug used in the treatment of pulmonary artery hypertension, via a combined virtual/experimental cocrystal screening. Abstract : We report the discovery of new cocrystals of bosentan, a drug used in the treatment of pulmonary artery hypertension, with succinic acid, resorcinol, and 4-hydroxybenzoic acid through a combined virtual/experimental cocrystal screening. The X-ray structure of the bosentan/succinic acid cocrystal shows a network of H-bonds involving both components, which have been studied energetically using DFT calculations. The succinic acid molecules interact with one of the pyrazine rings of bosentan establishing an energetically significant lp⋯π interaction. Moreover, they form homodimers stabilized by antiparallel CO⋯CO interactions. This set of interactions has been rationalized using molecular electrostatic potential (MEP) surfaces, the quantum theory of "atoms-in-molecules" (QTAIM), and the noncovalent interaction plot (NCIplot).